2007
DOI: 10.1016/j.jtcvs.2006.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Data acquisition for the histoculture drug response assay in lung cancer

Abstract: The histoculture drug response assay appears to be applicable to non-small cell lung cancer for the prediction of responses to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 16 publications
5
36
0
1
Order By: Relevance
“…In most of these previous systems, viability of tumors has been demonstrated for up to 7 days (13)(14)(15)(16)(17)(18)(19). Here, we identified a mild effect of cultivation after 24 hours of culture (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In most of these previous systems, viability of tumors has been demonstrated for up to 7 days (13)(14)(15)(16)(17)(18)(19). Here, we identified a mild effect of cultivation after 24 hours of culture (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…A number of organotypic culture systems have been previously developed for human tumors (13)(14)(15)(16)(17)(18). In most of these previous systems, viability of tumors has been demonstrated for up to 7 days (13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was equal or better than other studies on use of in vitro chemosensitivity assays in various cancers (Higashiyama et al, 2001;O'Toole et al, 2001;O'Toole et al, 2003;Yoshimasu et al, 2007). This result indicates that MTS is a preferable and convenient assay method for in vitro chemosensitivity test with malignant pleural effusion specimens from unresectable NSCLC patients.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, 8 parallel culture wells were designed to test the chemosensitivity of different parts of tumor specimen to avoid the issue of tumor heterogeneity. The efficacy rate for an individual agent using HDRA in vitro has a considerable good correlation with clinical response rate to each agent (30,31). Previous studies have reported that TS and DPD expression are correlated with fluorouracil sensitivity (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%